Biomedical image processing - Deserno, Thomas M.; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
In modern medicine, imaging is the most effective tool for diagnostics, treatment planning and therapy. Almost all modalities have went to directly digital acquisition techniques and processing of this image data have become an important option for health care in future. This book is written by a team of internationally recognized experts from all over the world. It provides a brief but complete overview on medical image processing and analysis highlighting recent advances that have been made in academics. Color figures are used extensively to illustrate the methods and help the reader to understand the complex topics.
Fundamentals of Biomedical Image Processing -- Part I: Image Formation -- Fusion of PET and MRI for Hybrid Imaging -- Cardiac 4D Ultrasound Imaging -- Part II: Image Enhancement -- Morphological Image Processing Applied in Biomedicine -- Medical Image Registration -- Part III: Feature Extraction and Selection -- Multi-Scale and Multi-Orientation Medical Image Analysis -- Feature Extraction and Selection for Decision Making -- Part IV: Segmentation -- Parametric and Non-Parametric Clustering for Segmentation -- Region-Based Segmentation: Fuzzy Connectedness, Graph Cut and Related Algorithms -- Model-Based Segmentation -- Part V: Classification and Measurements -- Melanoma Diagnosis -- CADx Mammography -- Quantitative Medical Image Analysis for Clinical Development of Therapeutics -- Part VI: Image Data Visualization -- Visualization and Diffusion MRI -- Part VII: Image Management and Integration -- Digital Imaging and Communications in Medicine -- PACS-Based Computer-Aided Detection and Diagnosis -- Content-Based Medical Image Retrieval -- Part VIII: Evaluation and Customizing -- Toolkits and Software for Developing Biomedical Image Processing and Analysis Applications -- Image Processing and the Performance Gap.
Electronic reproduction.
Keywords: Diagnostic imaging -- Data processing; Diagnostic imaging -- Digital techniques; Imaging systems in biology; Electronic books